Communication from the Expression Qualities System Perspective - Urban, Pavel (Communications - Scientific Letters of the University of Zilina, 2014)
The focus of this paper is to state a categorization of expressions for a qualitatively correct media communication. For our starting point, we have chosen the systematic categorization of aesthetic expression qualities based on the pragmatic aesthetics by Professor Frantisek Miko, which also constitutes the main scope of research for Institute of Literary and Art Communication at the Faculty of Arts of Constantine the Philosopher University in Nitra. However, our aim is to extend the original applicability of the aesthetic expression qualities categorization outside the artistic and aesthetic reality specifically for the use in the mass media environment. In other words, we aim to develop the existing methodology of the expression qualities system of the modern aesthetic categories - the so-called Nitra pragmatic aesthetics - on a media platform for the study of communication.
Keywords: expression qualities system; aesthetic categories; iconicism; operability; recipient